2002
DOI: 10.1097/00129492-200209000-00022
|View full text |Cite
|
Sign up to set email alerts
|

cDNA Microarray Analysis of Vestibular Schwannomas

Abstract: Our cDNA microarray analysis of schwannomas suggested several interesting and potentially important tumorigenesis pathways associated with vestibular schwannoma formation. Further in vivo study is necessary to define the roles of these identified genes and their potential relationships with the neurofibromatosis type 2 tumor suppressor gene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
85
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(88 citation statements)
references
References 58 publications
3
85
0
Order By: Relevance
“…Previous studies suggest that frequently reduced RBM5 levels exist in different types of tumors including breast cancer (25), schwannoma (26), and ~75% of primary lung cancers (27). We previously reported that the protein levels of RBM5 are lower in NSCLC compared with non-tumorous tissues (13).…”
Section: Discussionmentioning
confidence: 86%
“…Previous studies suggest that frequently reduced RBM5 levels exist in different types of tumors including breast cancer (25), schwannoma (26), and ~75% of primary lung cancers (27). We previously reported that the protein levels of RBM5 are lower in NSCLC compared with non-tumorous tissues (13).…”
Section: Discussionmentioning
confidence: 86%
“…Briefly, 5 μg of total RNA was primed with 500 ng of oligo(dT) [12][13][14][15][16][17][18] in a total of 12 μl reaction volume for 10 min. at 70°C followed by quick chill on ice.…”
Section: Rt-pcrmentioning
confidence: 99%
“…For example, H37 was identified as a serum antigen reacting with autologous antibody in renal cancer [13]. H37 is downregulated in human schwannomas [14] and in rastransformed Rat-1 embryonic fibroblasts [15]. Ectopic expression of H37 also suppresses growth of HT 1080 fibrosarcoma cells [15].…”
Section: Introductionmentioning
confidence: 99%
“…The RNA-binding motif protein 5 gene ( RBM5/LUCA-15/H37 ) encodes a protein containing two RRMs, two zinc fingers, one arginine-serine-rich domain (RS) and one glycine patch (G-patch) [15]. RBM5 and its paralog RBM6 are located in the human chromosome 3p21.3 region and were identified as candidate tumor suppressors of lung cancers and other solid tumors [1622]. RBM10 , another paralog of RBM5 , is also frequently mutated in lung adenocarcinoma samples [23].…”
Section: Introductionmentioning
confidence: 99%